2023
DOI: 10.1111/gbb.12848
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging related health phenotypes for polygenic prediction of impulsive choice, impulsive action, and impulsive personality traits in 1534 European ancestry community adults

Abstract: Impulsivity refers to a number of conceptually related phenotypes reflecting self‐regulatory capacity that are considered promising endophenotypes for mental and physical health. Measures of impulsivity can be broadly grouped into three domains, namely, impulsive choice, impulsive action, and impulsive personality traits. In a community‐based sample of ancestral Europeans (n = 1534), we conducted genome‐wide association studies (GWASs) of impulsive choice (delay discounting), impulsive action (behavioral inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…[24][25][26] These studies indicate a genetic component to discounting, but only a single gene (GPM6B) has ever show a genome-wide significant association with delay discounting. 23 Other studies have identified risk genes for impulsivity as the broadly defined construct, 7,27,28 but these genes did not have associations with delay discounting in Sanchez-Roige et al (2018). This lack of concordance underscores the modest overlap between questionnaire measures of impulsivity and delay discounting, and the broader uncertainty over the true relationship between delay discounting and complex neurobehavioral traits.…”
Section: Introductionmentioning
confidence: 98%
“…[24][25][26] These studies indicate a genetic component to discounting, but only a single gene (GPM6B) has ever show a genome-wide significant association with delay discounting. 23 Other studies have identified risk genes for impulsivity as the broadly defined construct, 7,27,28 but these genes did not have associations with delay discounting in Sanchez-Roige et al (2018). This lack of concordance underscores the modest overlap between questionnaire measures of impulsivity and delay discounting, and the broader uncertainty over the true relationship between delay discounting and complex neurobehavioral traits.…”
Section: Introductionmentioning
confidence: 98%